PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN TEMA 7 - Veni Nurman; Rizqa Ramadhani; Rahmad Wahyugi; Yanti Fitria; Desyandri Desyandri (Universitas Negeri Medan, 2020)
This study aimed to increase the learning outcomes by applying problem based laerning in class 4th SDN 13 IV Koto Aur Malintang. The subjects of this study amounted to 20 students. Data collection techniques used were observation, interview, and documentation. The data collected in this study were observational data of lesson plan, student and teacher activities in learning and test results. Data analysis techniques used descriptive qualitative analysis and quantitative analysis. The results of this study indicate an increase in learning outcomes. This was show from cycle I, II and III. The activities has increased compared to the pre-cycle. The results students activities meet the criteria for success of action, name ly the success of the learning process by students is said to be good, if every aspect of the observation sheet students all come up with information that has been carried out well and the average value of students is ≥ 70 and increases each cycle. Thus, the application of problem based learning can increase the learning outcomes in learning in grade IV of SDN 13 IV Koto Aur Malintang.Keywords: problem based learning, student learning outc